Status of the Prevention of Multidrug-Resistant Organisms in International Settings: A Survey of the Society for Healthcare Epidemiology of America Research Network. (7th November 2016) - Safdar, Nasia; Sengupta, Sharmila; Musuuza, Jackson S.; Juthani-Mehta, Manisha; Drees, Marci; Abbo, Lilian M; Milstone, Aaron M.; Furuno, Jon P.; Varman, Meera; Anderson, Deverick J.; Morgan, Daniel J.; Miller, Loren G.; et al.
Abstract : OBJECTIVE: To examine self-reported practices and policies to reduce infection and transmission of multidrug-resistant organisms (MDRO) in healthcare settings outside the United States. DESIGN: Cross-sectional survey. PARTICIPANTS: International members of the Society for Healthcare Epidemiology of America (SHEA) Research Network. METHODS: Electronic survey of infection control and prevention practices, capabilities, and barriers outside the United States and Canada. Participants were stratified according to their country's economic development status as defined by the World Bank as low-income, lower-middle-income, upper-middle-income, and high-income. RESULTS: A total of 76 respondents (33%) of 229 SHEA members outside the United States and Canada completed the survey questionnaire, representing 30 countries. Forty (53%) were high-, 33 (43%) were middle-, and 1 (1%) was a low-income country. Country data were missing for 2 respondents (3%). Of the 76 respondents, 64 (84%) reported having a formal or informal antibiotic stewardship program at their institution. High-income countries were more likely than middle-income countries to have existing MDRO policies (39/64 [61%] vs 25/64 [39%], P =.003) and to place patients with MDRO in contact precautions (40/72 [56%] vs 31/72 [44%], P =.05). Major barriers to preventing MDRO transmission included constrained resources (infrastructure, supplies, and trained staff) and challenges in changing provider behavior. CONCLUSIONS: In this survey, a substantial proportion of institutions reported encountering barriers to implementing key MDRO prevention strategies. Interventions to address capacity building internationally are urgently needed. Data on the infection prevention practices of low income countries are needed. Infect Control Hosp Epidemiol. 2016:1–8